TEKNIK PERMAINAN CONNECT FOUR DALAM MENINGKATKAN KEMAMPUAN MENULIS KALIMAT SEDERHANA BAHASA PERANCIS - Ridwan, Rizki Muhammad (2017)
This study aims to describes (1) the effectiveness of using Connect Four game techniques in learning of writing simple sentences in French, (2) the learning outcomes of students in writing simple sentences in French before and after using Connect Four game techniques, and (3) the response of the students after using the techniques of the game Connect Four in learning to write simple sentences in French. In practice the methods used in this research is pre-experimental research method with one group pretest-posttest design. Data collection techniques used are the study of the literature, test and question form. Samples taken in this study is the characteristic ability of 32 wrote simple sentences in French, students of Class XI IPS 5 SMA Negeri 6 of Academic Year 2016/2017. Referring to the statistical calculation, obtained a value of t count of 3.90. Significance levels used in this study is 1% with degrees of freedom (d. b) of 31, then retrieved the value of the t table of 2.45 meaning t count > t table. Based on this, then the hypothesis in this study can be accepted, meaning that it can be used to enhance the ability to write simple sentences in French students of Class XI IPS 5 SMA Negeri 6 of Academic Years 2016/2017. In addition, refer to the results of the study, the results of the analysis of the test data has increased, the average value of student's pretest is 6.54 of the maximum value of 10 and the average value of student's posttest become 8.02, so there's an increase in value of 1,48. This indicates the existence of a significant outcome ifferences before and after using Connect Four game technique in learning to write simple sentences in French. Then, based on the results of the analysis of the question form, 71% of students feel happy and helpful in learning to write simple sentences in French after using Connect Four game technique.;---Penelitian ini bertujuan untuk mendeskripsikan (1) tingkat efektivitas penggunaan teknik permainan Connect Four dalam pembelajaran menulis kalimat sederhana bahasa Perancis siswa, (2) hasil belajar siswa dalam menulis kalimat sederhana bahasa Perancis sebelum dan setelah menggunakan teknik permainan Connect Four, dan (3) tanggapan siswa setelah menggunakan teknik permainan Connect Four dalam pembelajaran menulis kalimat sederhana bahasa Perancis. Dalam pelaksanaannya metode yang digunakan dalam penelitian ini ialah metode pre-experimental dengan desain penelitian one group pretest-posttest. Teknik pengumpulan data yang digunakan yaitu studi pustaka, tes dan angket. Sampel yang diambil dalam penelitian ini ialah karakteristik kemampuan menulis kalimat sederhana bahasa Perancis siswa kelas XI IPS 5 SMA Negeri 6 Cimahi Tahun Pelajaran 2016/2017. Mengacu pada perhitungan statistik, diperoleh nilai thitung sebesar 3,90. Taraf signifikansi yang digunakan dalam penelitian ini ialah 1% dengan derajat kebebasan (d.b) sebesar 31, maka diperoleh nilai ttabel sebesar 2,45 yang berarti thitung > ttabel. Berdasarkan hal tersebut, maka hipotesis dalam penelitian ini dapat diterima, artinya dapat digunakan untuk meningkatkan kemampuan menulis kalimat sederhana bahasa Perancis siswa kelas XI IPS 5 SMA Negeri 6 Cimahi Tahun Pelajaran 2016/2017. Selain itu, merujuk pada hasil penelitian, hasil analisis data tes mengalami peningkatan, nilai rata-rata prates siswa sebesar 6,54 dari nilai maksimal 10 dan nilai rata-rata pascates siswa menjadi 8,02, sehingga terdapat peningkatan nilai sebesar 1,48. Hal ini menunjukkan adanya perbedaan hasil yang cukup signifikan sebelum dan setelah penggunaan teknik permainan Connect Four dalam pembelajaran menulis kalimat sederhana bahasa Perancis. Lalu, berdasarkan hasil analisis angket, 71% siswa merasa senang dan terbantu dalam pembelajaran menulis kalimat sederhana bahasa Perancis setelah menggunakan teknik permainan Connect Four.